2019
DOI: 10.1038/s41467-019-10177-1
|View full text |Cite
|
Sign up to set email alerts
|

Wwp2 maintains cartilage homeostasis through regulation of Adamts5

Abstract: The WW domain-containing protein 2 ( Wwp2 ) gene, the host gene of miR-140, codes for the Wwp2 protein, which is an HECT-type E3 ubiquitin ligases abundantly expressed in articular cartilage. However, its function remains unclear. Here, we show that mice lacking Wwp2 and mice in which the Wwp2 E3 enzyme is inactivated (Wwp2-C838A) exhibit aggravated spontaneous and surgically induced osteoarthritis (OA). Consistent with this phenotype, WWP2 expression level is down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 60 publications
2
73
3
Order By: Relevance
“…A more precise analysis of Wwp2 and miR-140 recently reported that Wwp2 mutant mice had no craniofacial abnormalities [53], in contrast to a previous study that observed impaired skull formation in Wwp2-KO mice [54]. Together, these results indicate that miR-140, rather than Wwp2, is crucial for craniofacial development and chondrogenesis in addition to its suggested role in cartilage homeostasis [55]. These investigations highlight the difficulties in dissecting the functions of host genes and their miR.…”
Section: Micro-rna 140 (Mir-140) and Osteoarthritismentioning
confidence: 78%
“…A more precise analysis of Wwp2 and miR-140 recently reported that Wwp2 mutant mice had no craniofacial abnormalities [53], in contrast to a previous study that observed impaired skull formation in Wwp2-KO mice [54]. Together, these results indicate that miR-140, rather than Wwp2, is crucial for craniofacial development and chondrogenesis in addition to its suggested role in cartilage homeostasis [55]. These investigations highlight the difficulties in dissecting the functions of host genes and their miR.…”
Section: Micro-rna 140 (Mir-140) and Osteoarthritismentioning
confidence: 78%
“…A more precise analysis of Wwp2 and miR-140 recently reported that Wwp2 mutant mice had no craniofacial abnormalities [47], in contrast to another study that observed impaired skull formation in miR-140 KO mice, as well as in Wwp2 and miR-140 double KO mice [47]. Together, these results indicate that miR-140, rather than Wwp2, is crucial for craniofacial development and chondrogenesis, in addition to its suggested role in cartilage homeostasis [49]. These investigations highlight the difficulties in dissecting the functions of host genes and their microRNA.…”
Section: Mir-140 and Osteoarthritismentioning
confidence: 78%
“…26,27 Currently, WWP2 is considered to be involved in various life activities, such as development and ossification. 16,[19][20][21][22] In previous studies, WWP2 was discovered to be highly expressed in diabetic cardiomyopathic heart. 28 In primary cardiac fibroblasts, TGFβ1 irritates the N-terminal subtype of WWP2 to enter the nucleus, subsequently strengthening the activity of WWP2-FL to promote the combining with Smad2, and may promote its monoubiquitination, thus activating the downstream Pro-fibrogenic gene programme.…”
Section: Discussionmentioning
confidence: 99%
“…The E3 ubiquitin ligase WWP2 controls many biological processes such as the cell cycle, cell division, immune response, antigen presentation, apoptosis and cell signalling. [16][17][18][19] WWP2 not only degrades substrates, but also regulates genes post-transcriptionally. 20 Studies have demonstrated that WWP2 dysfunction can cause many diseases, including maxillofacial deformity, skeleton damage and embryonic dysplasia.…”
mentioning
confidence: 99%